THE IMPACT OF SOCIAL MEDIA ADVERTISING ON BUYING BEHAVIOR OF CONSUMERS (International Journal of Food and Nutritional Sciences, 2022)
Consumer purchasing behaviour, also known as consumer decision making, is the process by which individuals search for, select, purchase, use, and dispose of goods and services to satisfy required needs. Consumers search for, select, purchase, use, and dispose of these items in order to fulfil their requirements. The primary objective of this research project is to provide a solution to the primary issue regarding the impact of social media advertising on consumer purchasing behaviour in a particularly dynamic area, namely the fashion retail business, and then to determine the differences if any existed in this relation with regard to the names of the brands as well as the demographic aspects of the consumers. The findings of the electronic questionnaires that were given to consumers who live in Raipur, India revealed a moderate relation for both buying decisions and post-purchase behaviour, as those steps represent the five steps need recognition model in consumer buying behaviour. The questionnaires revealed that there was a weak relation between social media advertising and consumer need recognition, that there was no relation at all with search for information, that there was a strong relation with evaluate the alternatives, and that there was no relation at all with post-purchase behaviour. In addition, the data demonstrated that there were no variations in this association with regard to the age of the customer or their degree of education. On the other hand, there were differences between males and females in terms of the relationship between consumer need awareness and information search. In addition, additional modifications have been made with regard to income between social media advertising and evaluating the alternatives, particularly for customers who make more than 20,000 INR among the various income levels.